Even the losers: five-year distribution dynamics of alien plant species in South African savanna - Petr Pyšek; Jan Čuda; Llewellyn C. Foxcroft; Klára Pyšková; Martin Hejda (NeoBiota)
We studied the short-term dynamics of the occurrence of alien plant species in a South African savanna. Within the MOSAIK (Monitoring Savanna Biodiversity in the Kruger National Park) project, plant species were recorded in a representative set of 60 plots, 50 m × 50 m in size, across the entire KNP in 2019–2020, distributed to cover a range of savanna habitats, i.e. perennial rivers, seasonal rivers and dry crests. The sampling focusing on alien plants was carried out in the same plots in 2024 and the changes in distribution patterns that occurred over the 4–5 years since the first sampling were assessed. In the first sampling period, 23 alien species were recorded and, in the second sampling, 20 were recorded; this gives a total of 25 alien species over the whole period of 2019–2024. In the recent survey, Alternanthera pungens, Conyza bonariensis, Gomphrena celosioides, Bidens biternata and Achyranthes aspera were most widespread, present in at least 10 plots. Using log-linear models, we showed that the total number of alien species records in plots did not significantly differ between the two sampling periods, indicating the absence of trends in species richness for the alien flora of KNP. There was a highly significant effect of habitat, with sites at perennial rivers harbouring more alien species than those at seasonal rivers and on crests. We also found a marginally significant interaction of habitat and sampling period, reflecting that the dry crests currently harbour fewer aliens than in 2019–2020. The frequency of some of the most invasive KNP species, such as Parthenium hysterophorus, Xanthium strumarium and Opuntia stricta, remained basically the same. However, Conyza bonariensis is an alien species that was quite rare in studied plots in 2019–2024, but its presence dramatically increased and it became widespread and locally abundant beyond the surveyed plots in some parts of KNP. Although not too successful until a few years ago, this species represents a future plant invasion threat in KNP.